2003
DOI: 10.1210/jc.2002-021085
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Functional Estrogen Receptors in Human Fetal Male External Genitalia

Abstract: It is generally assumed that male genital development is determined by androgens on a default program leading to female genitalia. Female genitalia virilization is due to high levels of androgens, whereas feminization is linked to reduction or lack of fetal androgen. Excess androgen determines sex reversion in female, whereas excess estrogen does not cause male feminization. In the present study, we investigate the presence of androgen receptors (AR) and estrogen receptors (ER) in human fetal penile tissue and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
50
0
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(56 citation statements)
references
References 48 publications
4
50
0
2
Order By: Relevance
“…On the other hand, the importance of estrogens in male reproductive tract development has been increasingly acknowledged. Functional Estrogen Receptors (ESR)s were detected in differentiating male external genitalia localized at the same structures as the androgen receptors, indicating interactions between effects exerted by the two steroid hormones (7,8); and an excess of estrogens in the developing murine urethra results in an inhibition of the cell proliferation in a dose-dependent manner (9). Moreover, hypospadias has been induced in a mice model by maternal exposure to synthetic estrogens during pregnancy (10).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the importance of estrogens in male reproductive tract development has been increasingly acknowledged. Functional Estrogen Receptors (ESR)s were detected in differentiating male external genitalia localized at the same structures as the androgen receptors, indicating interactions between effects exerted by the two steroid hormones (7,8); and an excess of estrogens in the developing murine urethra results in an inhibition of the cell proliferation in a dose-dependent manner (9). Moreover, hypospadias has been induced in a mice model by maternal exposure to synthetic estrogens during pregnancy (10).…”
Section: Introductionmentioning
confidence: 99%
“…We also found that estrogen and androgen receptors did not have a special side of expression among the prepuce, glans and, urethral plate. Estrogen and androgen receptors are present in developing human fetal penile tissue and both are localized in the same structures of male external genitalia [1,2,4,7,9]. There is also a hormonal balance between androgen and estrogen which exists during the formation of the genital tubercle [1,4,8].…”
Section: Discussionmentioning
confidence: 99%
“…Estrogen and androgen receptors are present in developing human fetal penile tissue and both are localized in the same structures of male external genitalia [1,2,4,7,9]. There is also a hormonal balance between androgen and estrogen which exists during the formation of the genital tubercle [1,4,8]. Therefore, dominant expression of estrogen receptors (42%) when compared to androgen receptors (21%) in penile tissues of children with hypospadias may be the postnatal finding of disrupted estrogen and androgen receptor interaction during the intrauterine development of external genitalia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[20][21][22][23] The finding of estrogen receptors in the male reproductive tract during development raises the possibility that estrogens may also influence the risk for hypospadias. 24 Currently, four hypospadias genes have been identified, namely the Mastermind-like Domain-containing 1 gene (MAMLD1/CXorf6), the Activating Transcription Factor 3 (ATF3) gene, the Diacylglycerol kinase kappa (DGKK) gene and most recently the basonuclin 2 (BNC2) gene. [25][26][27][28] In our search for hypospadias candidate genes, we previously performed a genome-wide linkage scan in 69 families with at least two affected family members.…”
Section: Introductionmentioning
confidence: 99%